2010
DOI: 10.1016/j.jflm.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The socio-demographic profile of hanging suicides in Ireland from 1980 to 2005

Abstract: Abstract.This paper provides a comparison of the socio-demographic profile of hanging suicides and suicides by other means in Ireland from January 1 st 1980 to December 31st 2005. Data on 9674 suicides occurring in that time frame was provided by the Central Statistics Office of Ireland (CSO). 4031 (42%) of these deaths involved suicide by 'hanging, suffocation or strangulation' (HSS), with the remainder being suicides by other means. Binary logistic regressions were used to examine 6 potential risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Variation was apparent, with the City of Dublin having lower rates of self-harm than other Irish cities, despite being the most urbanized After adjusting for fragmentation and deprivation, a small, but significant residual relationship remained between urban environment and self-harm. Deprivation was the strongest area-level predictor of self-harm Mitchell, Popham (2008) [ 44 ] National Office for Statistics (2001–2005) 366,348 events (males and females, resident in England) Quantity of green space Deaths recorded as intentional self-harm No differences in rates of suicidality and self-harm between urban–rural environments No interactions between socioeconomic deprivation and environment were found in relation to suicidality and self-harm and living environment O’Reilly, Rosato, Connolly, Cardwell (2008) [ 45 ] Northern Ireland Statistics and Research Agency (2001–2006) 566 events/persons (Males and females, 16–74 years, resident in Northern Ireland) Population density Death recorded as suicide No significant relationship was found between population density and suicide risk Indicators of socioeconomic disadvantages were strongly related to suicide risk, with higher rates in socially fragmented and deprived areas, with population density no longer apparent in the fully adjusted model Sarma, Kola (2010) [ 46 ] Central Statistics Office of Ireland (1980–2005) 9,674 events/persons (males and females, resident in Ireland) Place of residence Death recorded as suicide Those completing suicide by hanging were more likely to be rural dwelling Cooper et al (2010) [ 47 ] Emergency department records across three general hospitals (2001–2006) 14,997 persons (males and females, 16–64 years seeking treatment in Oxford, Manchester, or Derby) Cities of Oxford, Manchester, and Derby Self-harm presentations to emergency departments ↑* Young, black females Harriss, Hawton (2011) [ 48 ] Oxford Monitoring System for Attempted Suicide (2001–2005) 4054 persons, 6833 events (40.6% male, > 15 years, residence in Oxford, England) Populat...…”
Section: Resultsmentioning
confidence: 99%
“…Variation was apparent, with the City of Dublin having lower rates of self-harm than other Irish cities, despite being the most urbanized After adjusting for fragmentation and deprivation, a small, but significant residual relationship remained between urban environment and self-harm. Deprivation was the strongest area-level predictor of self-harm Mitchell, Popham (2008) [ 44 ] National Office for Statistics (2001–2005) 366,348 events (males and females, resident in England) Quantity of green space Deaths recorded as intentional self-harm No differences in rates of suicidality and self-harm between urban–rural environments No interactions between socioeconomic deprivation and environment were found in relation to suicidality and self-harm and living environment O’Reilly, Rosato, Connolly, Cardwell (2008) [ 45 ] Northern Ireland Statistics and Research Agency (2001–2006) 566 events/persons (Males and females, 16–74 years, resident in Northern Ireland) Population density Death recorded as suicide No significant relationship was found between population density and suicide risk Indicators of socioeconomic disadvantages were strongly related to suicide risk, with higher rates in socially fragmented and deprived areas, with population density no longer apparent in the fully adjusted model Sarma, Kola (2010) [ 46 ] Central Statistics Office of Ireland (1980–2005) 9,674 events/persons (males and females, resident in Ireland) Place of residence Death recorded as suicide Those completing suicide by hanging were more likely to be rural dwelling Cooper et al (2010) [ 47 ] Emergency department records across three general hospitals (2001–2006) 14,997 persons (males and females, 16–64 years seeking treatment in Oxford, Manchester, or Derby) Cities of Oxford, Manchester, and Derby Self-harm presentations to emergency departments ↑* Young, black females Harriss, Hawton (2011) [ 48 ] Oxford Monitoring System for Attempted Suicide (2001–2005) 4054 persons, 6833 events (40.6% male, > 15 years, residence in Oxford, England) Populat...…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a study in Ireland showed that it can also be a rural phenomenon, in which deaths due to hanging were statistically significant in the male, single, rural dwelling and agriculturally employed. 22 Falls from buildings are the commonest in Australia, with falls from ladders predominantly high in falls occurring at home. 23 The distribution of injuries for accidental deaths at home were contributed by home repairs, gardening, gutter cleaning and painting, and the group affected were mainly in the mean age of 53.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions were more intense on the left side CT scan of the neck -reveal normal cervical spine vertebras, normal spinal cord absence of the larynx-posts-surgery, no hyoid bone -consequence of the surgery -total laryngectomy, we perform a suprahyoid resection imposed by the tumoral extensions. Also, no lymph nodes were visible, the large vessels of the neck present, visible with the contrast iv substance, except IJV on the right size [11][12][13][14][15]. CT scan of the thorax describe tracheal tube and diffuse bilateral opacities -bilateral bronchopneumonia (Figure 6).…”
Section: Case Reportmentioning
confidence: 99%
“…In humans, neck seems to be a fragile part of the body, exposed to traumas the mains characteristics resulting from his anatomy are relatively small diameter, lack of bony shielding, and vital structures like airways, spinal cord, and major vessels, all representing vulnerabilities, high risk of lethal traumas [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Neck is joining head and trunk and limited by lower margin of corpus mandible, back margin of ramus mandible, porus acusticus externus, apex of mastoid bone and superior nuchal line on the top.…”
Section: Introductionmentioning
confidence: 99%